Dual inhibition of mTOR pathway and VEGF signalling in neuroendocrine neoplasms: From bench to bedside. Issue 9 (November 2015) - Cella, Chiara Alessandra; Minucci, Saverio; Spada, Francesca; Galdy, Salvatore; Elgendy, Mohamed; Ravenda, Paola Simona; Zampino, Maria Giulia; Murgioni, Sabina; Fazio, Nicola
Graphical abstract: In neuroendocrine tumours, mTOR pathway plays a central role with VEGF signalling pathway and Met upregulation, stimulating cell proliferation, survival and angiogenesis: under hypoxia conditions, the HIF upregulation induces mTOR activation by TSC1/2, VEGF production and Met upregulation through CRCX4. Highlights: Clinical trials reported a potential synergistic effect of sunitinib in combination to rapalogs in some advanced cancers. Several VEGF pathway inhibitors have shown clinical activity in NENs. Sunitinib exhibits a weak cytotoxic activity due to its inhibitory effect on VEGFR2 signalling. Inhibition of Akt/mTOR signalling sensitises resistant cancer cells to treatment with sunitinib. We discuss the role of dual blockade of VEGF and mTOR pathway, focusing on current studies and future perspectives. Abstract: After years of limited progress in the treatment of neuroendocrine neoplasms (NENs), an increasing number of therapeutic targets have recently emerged as potential tools to improve disease outcome. The mammalian target of rapamycin (mTOR) pathway and vascular endothelial growth factor (VEGF) signalling are implicated in the regulation of cell growth, proliferation, neo-angiogenesis and tumour cell spread. Their combined blockade, in a simultaneous or sequential strategy, represents an intriguing biological rationale to overcome the onset of resistance mechanisms. However, is becoming increasingly imperative to find the optimal sequential strategy according to the best toxicity profile, and also to identify predictive biomarkers. We will provide an overview of the pre-clinical and clinical data relating to mTOR pathway/VEGF signalling as a potential targets of treatment in NENs.